AFIKS DALAM BAHASA DONDO DIALEK TIALO DI KECAMATAN MOUTONG KABUPATEN PARIGI MOUTONG - Azim, Aliyul; Supriyadi, Supriyadi; Hinta, Ellyana (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2025)
Affixation is one of the processes of attaching morphemes to a base form. This study aims to (1) describe the types of affixes in the Dondo language, Tialo dialect, in Moutong Subdistrict, Parigi Moutong Regency, and (2) explain the affixation process in the Dondo language, Tialo dialect, in the same region. This study used a qualititative descriptive method in Moutong Subdistrict, Parigi Moutong Regency. The data sources were informants from Lobu Village and Tuladenggi Pantai Village in Moutong Subdistrict, referring to 200 Swadesh vocabulary items. Data collection techniques included interviews, observation, elicititation (conservation), and recording. The results of this study indicate that (1) the types of affixes found in the Dondo language, Tialo dialect, include 17 prefixes (mo-, mon-, mom-, moku-, mong-, me-, meg-, men-, mem-, mengk-, no-, o-, po-, pom-, pon-, pe’- and pem-,) there infixes(-k-, -an-, and –o-), seven suffixes (-onyo, -a’a, -ane, -one, -ma’a, -mo, and -tutu), and one circumfix (no-mo). (2) The process of affixation whether through prefixation, infixation, suffixation, or circumfixation, results in thr formation of new words in the Dondo language, Tialo dialect. In conclusion, affixation in the Dondo language, Tialo dialect, leads to morphological changes in base words, resulting in derived words. This transformation is evident in the collected data, where the initial 200 Swadesh vocabulary items were reduced to 111 derived words.